beta-Microseminoprotein binds CRISP-3 in human seminal plasma. - Udby, L; Lundwall, A; Johnsen, A; Fernlund, P; Valtonen-André, C; Blom, A; Lilja, H; Borregaard, N; Kjeldsen, L; Bjartell, A (2005)
beta-Microseminoprotein (MSP) and cysteine-rich secretory protein 3 (CRISP-3) are abundant constituents of human seminal plasma. Immunoprecipitation and gel filtration of seminal plasma proteins combined with examination of the proteins in their pure form showed that MSP and CRISP-3 form stable, non-covalent complexes. CRISP-3 binds MSP with very high affinity, as evidenced by surface plasmon resonance. Due to far higher abundance of MSP in prostatic fluid, it manifests large overcapacity for CRISP-3 binding. Structural similarity with an MSP-binding protein from blood plasma suggests that CRISP-3 binds MSP through its aminoterminal SCP-domain.